Carcinogenesis and aging - Anisimov, Vladimir N. (Henry Stewart Talks, 2017)
Historical journey into carcinogenesis and aging, Age and susceptibility to carcinogens, Cell senescence and cancer, Multi-stage carcinogenesis and aging, Geroprotectos and cancer